State capacity and growth in Sub-Saharan Africa: a dynamic panel examination of the pillars of prosperity - Adaid, Felipe A. P.; Banda, Lloyd George; Chirwa, Joseph Amazuwa; Chidzanja, Chikondi; Mavhura, Bathromeu (Frontiers in Political Science, 2025)
This paper investigates Smith's triumvirate hypothesis that peace, easy taxes, and a tolerable administration of justice inclusively constitute what a state requires to attain the highest degree of economic prosperity. First, the paper constructed a single index of Smith's triumvirate through a principal component analysis (PCA). Then, data analysis using a two-step difference GMM technique was conducted, with results confirming the hypothesis in Sub-Saharan Africa.